Are farmers’ minds really too elusive to capture? A novel evaluation framework for the knowledge transfer initiatives in agriculture - Ana Novak; Tanja Šumrada; Luka Juvančič (International Journal of Agricultural Sustainability)
Knowledge transfer initiatives aim to improve farmers’ knowledge and skills for tackling the growing economic, environmental and social challenges in agriculture. However, their evaluation is often inadequate due to institutional barriers and a lack of comprehensive methodology for assessing normative and behavioural shifts within this social group. To address this gap, we developed an extended evaluation framework for the knowledge transfer activities within the European Union's Common Agricultural Policy (CAP), including three indicators levels: output, result and impact. The indicators and survey instruments were based on the Theory of Planned Behaviour and piloted in a selected EU Member State for evaluating knowledge transfer measures in the programming period 2014–2022. The results indicate a promising potential of the proposed framework for capturing the multifaceted outcomes of knowledge transfer activities in agriculture. The usefulness and feasibility of the evaluation framework were further assessed through interviews with AKIS actors. They highlighted that evaluation activities at the Member State level may be hindered by inconsistent long-term data collection, insufficient response and involvement of farmers, deviations from the agreed protocols and a lack of dedicated resources. To ensure the uptake of the proposed evaluation framework, evaluation culture within the managing authorities and among stakeholders should be systematically fostered at the Member State level. This process can be enhanced by adopting a more elaborated CAP monitoring framework and methodology guidelines and by providing targeted training on evidence-driven policy-making.